Pengaruh Sektor Pariwisata Terhadap Perekonomian dan Keruangan Kota Bukittinggi (Pendekatan Analisis Input Output) - Desi Arianti (Jurnal Wilayah dan Lingkungan, 2014)
Bukittinggi city is one of the city located in the province of West Sumatra .  Although it does not have the potential of natural resources that can be exploited , Bukittinggi has another potential, which is a beautiful natural conditions, the air is cool, has a historic heritage places, and is located in a strategic position potentially make this city as tourists visiting the area.  Because of the potential of the tourism sector serve as a leading sector in the city of Bukittinggi, which is expected to be the main driver of the city economy.  This research was conducted with input-output analysis approach , to examine how the influence of the tourism sector and linkages with other sectors of the economy of the town of Bukittinggi.  Moreover it will be seen also how the spatial effect of the tourism sector on the pattern and structure of urban space Bukittinggi. The influence of the tourism sector to the economy of Bukittinggi shows the role of the tourism sector to the total demand is 40.86% when grouped into the business field of agriculture and mining sector, industrial sector, tourism sector and the service sector. Linkages with other sectors of the tourism sector seen from the spread of the power index and the degree of sensitivity, all sectors related to tourism activities have spread of power index > 1.  But the degree of sensitivity index > 1 only occurs in large & retail trade sector and the transport, while the hotel secto , restaurants and entertainment and recreation has index < 1.  Multiplier effect of all relevant sectors of tourism activities have a relatively large effect on both the output multiplier effects, household income and employment.  Application of financial input scenarios, showing the influence of the tourism sector on the economy will be larger Bukittinggi if allocated greater financial inputs to the sectors of tourism, both in the form of government spending and investment spending.  The existence of attractions around the city center has affected the structure of the city, where the activity and tourism-related businesses keen to be located closer to attractions.  However, the pattern of urban development to the east, north and south of the city is more influenced by the presence of the road network.